Does gender matter in credit denial among small and medium scale enterprises in Ghana?. (4th February 2020) - Baidoo, Samuel Tawiah; Sakyi, Daniel; Aidoo, Jacob Benson
The role played by small and medium scale enterprises (SMEs) in employment creation, economic growth and poverty reduction of the developing world cannot be overemphasised. However, the ability of these enterprises to access credit in order to expand their businesses has for years remain a key challenge. Past studies on credit denial among SMEs have emphasised firms' characteristics with little emphasis on firm owners' characteristics such as gender. The present study revisits previous studies and provides evidence supporting our hypothesis that gender matters in credit denial among SMEs. The study relies mainly on primary data and applies the binary probit estimation technique to the dataset. The study reveals among others that owners of small and medium scale enterprises who are females are less likely to be denied credit. Given the findings, recommendations and relevant policy implications are provided.